2021
DOI: 10.5423/ppj.oa.10.2020.0192
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Genetic Diversity and Population Structure of Hemileia vastatrix from Peruvian Coffee Plantations

Abstract: Population genetic studies of Hemileia vastatrix have been conducted in order to describe the evolutionary dynamics of the pathogen and the disease epidemiology as consequence of changes in disease management and host distribution occurred in Peru after the 2013 epidemic. These analyses were performed by sequencing the internal transcribed spacers of the nuclear ribosomal DNA (rDNA-ITS) of H. vastatrix collected from two coffee growing areas in 2014 and 2018. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
1
0
0
Order By: Relevance
“…Furthermore, the unstructured population of H. vastatrix could result from asexual reproduction ( Ramírez-Camejo et al, 2021 ). The results of this study are similar to those from studies in the coffee-growing regions of Peru and Brazil ( Maia et al, 2013 ; Cabral et al, 2016 ; Quispe-Apaza et al, 2017 , 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the unstructured population of H. vastatrix could result from asexual reproduction ( Ramírez-Camejo et al, 2021 ). The results of this study are similar to those from studies in the coffee-growing regions of Peru and Brazil ( Maia et al, 2013 ; Cabral et al, 2016 ; Quispe-Apaza et al, 2017 , 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…However, the diversity of the H. vastatrix population may be subject to selection pressure from the resistance genes of the cultivated coffee cultivars, which could lead to the introduction of new pathogen variations. As a result, there is currently a good chance that new pathogen variations will appear [50]. Therefore, it is crucial to investigate the genetic diversity and population structure of plant pathogens in order to monitor pathogen evolution, create disease control measures, and understand fungal epidemiology [41].…”
Section: Discussionmentioning
confidence: 99%
“…Studies focused on determining coffee genotypes susceptible or resistant to rust and their respective degrees of severity are carried out largely in the field, taking advantage of natural conditions for the disease spread (Julca-Otiniano et al, 2019;Gutiérrez-Calle et al, 2021;Dilas-Jiménez et al, 2022), uncontrolled conditions that could influence the results. These studies also focus on determining the genetic diversity of H. vastatrix and its distribution area (Gamarra et al, 2021;Quispe-Apaza et al, 2021;Le et al, 2022;Ramírez-Camejo et al, 2022). Studies have also been reported where genotypes of interest are evaluated under greenhouse conditions using a H. vastatrix uredospore suspension obtained from infected coffee leaves of plants in field (Bustamante et al, 2001;Paredes-Espinosa et al, 2023).…”
Section: Introductionmentioning
confidence: 99%